2014
DOI: 10.1097/mph.0b013e31829d4900
|View full text |Cite
|
Sign up to set email alerts
|

Therapy of Advanced-stage Mature B-cell Lymphoma and Leukemia in Children and Adolescents With Rituximab and Reduced Intensity Induction Chemotherapy (B-NHL 2004M Protocol)

Abstract: Pediatric mature B-cell non-Hodgkin lymphomas (B-NHLs) are highly aggressive malignant tumors that are curable with chemotherapy (ChT). High-dose methotrexate (MTX) is considered indispensable for successful treatment, but this therapy frequently induces severe mucositis and infectious complications, especially in induction, which can cause treatment failure. A prospective multicenter trial of combined immunochemotherapy for advanced-stage B-NHL with rituximab and the modified NHL-BFM-90 protocol was conducted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
25
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 10 publications
5
25
0
1
Order By: Relevance
“…Patients with mature B-cell lymphomas were treated according to modified BFM-NHL 2010 core protocol chemotherapy and rituximab (13), peripheral T-cell lymphomas were treated according to individual schemes, leukemias were treated according to approved MB-ALL2008 or ALL-BFM-2005 protocols. A reduction of doses was implemented in seven patients, the majority (13 patients) received non-reduced chemotherapy with no significant toxicity.…”
Section: Resultsmentioning
confidence: 99%
“…Patients with mature B-cell lymphomas were treated according to modified BFM-NHL 2010 core protocol chemotherapy and rituximab (13), peripheral T-cell lymphomas were treated according to individual schemes, leukemias were treated according to approved MB-ALL2008 or ALL-BFM-2005 protocols. A reduction of doses was implemented in seven patients, the majority (13 patients) received non-reduced chemotherapy with no significant toxicity.…”
Section: Resultsmentioning
confidence: 99%
“…This approach could avoid the need to increase the dose intensity of drugs with multiorgan toxicity. A prospective study in Russian children showed that using rituximab in early therapy of mature B‐cell neoplasms resulted in a 5% induction death rate and an overall survival of 82% . However, the relatively high cost of rituximab may restrict its use in limited‐resource settings.…”
Section: Discussionmentioning
confidence: 99%
“…There is a small subset of BL presents in stage I and II (limited stage) and this small population has a better outcome than those with advanced stage . The outcome of patients with advanced stage has improved in the recent era owing to the use of more intense chemotherapy regimens, the availability of rituximab, the application of antiretroviral therapy (ART), and improvements in supportive care . However, it is unclear whether the recent changes in management modalities have affected the survival of limited‐stage BL patients who already had excellent cure rates.…”
Section: Introductionmentioning
confidence: 99%